PENGUATAN LITERASI DAN NUMERASI BAGI GURU MELALUI PELATIHAN PENINGKATAN KOMPETENSI GURU DI SEKOLAH DASAR NEGERI PULO PANJANG 1 - Ulinnuha Ulinnuha; Rina Andriani; Desma Yuliadi Saputra; Syamsul Hidayat (Jurnal Abdimas Bina Bangsa, 2024)
This community service aims to provide training related to strategies for strengthening literacy and numeracy. Participants are expected to be able to apply strategies to strengthen literacy and numeracy; text-rich environment development, social emotional development, and academic environment development. Participants in this activity were the principal, teachers and 4 students of SDN Pulo Panjang 1 with a total of 20 participants. The methods used in this service are, observation, interviews, socialization, training and simulation. This community service has made a positive contribution in efforts to increase teacher competency by implementing creative, fun and meaningful strategies for strengthening iteration and numeration. (1) This PKM activity is able to provide alternative solutions to overcome the problem of students' difficulty understanding the material. So that students are enthusiastic and eager to take part in all subjects, (2) Participants understand strategies for strengthening literacy and numeracy (3) School principals, teachers and librarians are motivated to be optimistic about implementing literacy movements despite the remote geographical conditions of educational units